2021
DOI: 10.3390/life11020175
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Phenotypes and Chronic Kidney Disease: A Cross-Sectional Assessment of Patients from a Large Federally Qualified Health Center

Abstract: The purpose of this study is to determine if renal function varies by metabolic phenotype. A total of 9599 patients from a large Federally Qualified Health Center (FQHC) were included in the analysis. Metabolic health was classified as the absence of metabolic abnormalities defined by the National Cholesterol Education Program Adult Treatment Panel III criteria, excluding waist circumference. Obesity was defined as body mass index >30 kg/m2 and renal health as an estimated glomerular filtration rate (eGFR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Kouvari et al reported a large percentage of the MHN phenotype (36.30%) in the relatively homogenous Greek population assessed in the ATTICA cohort study [ 11 ], which is almost double the frequency of the MHN in the present study. Our prior research identified a large percentage of the MUO phenotype (57.79%) in a federally qualified health center in the southern U.S. [ 23 ], which is 1.5 times the proportion that we established here. The sample used in the present study is representative of the entire U.S. population and therefore consists of greater racial and ethnic diversity than the study by Kouvai et al as well as greater socioeconomic and geographic diversity than our prior study.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Kouvari et al reported a large percentage of the MHN phenotype (36.30%) in the relatively homogenous Greek population assessed in the ATTICA cohort study [ 11 ], which is almost double the frequency of the MHN in the present study. Our prior research identified a large percentage of the MUO phenotype (57.79%) in a federally qualified health center in the southern U.S. [ 23 ], which is 1.5 times the proportion that we established here. The sample used in the present study is representative of the entire U.S. population and therefore consists of greater racial and ethnic diversity than the study by Kouvai et al as well as greater socioeconomic and geographic diversity than our prior study.…”
Section: Discussionmentioning
confidence: 77%
“…Our primary outcomes indicate that the strictly defined MUN phenotype accounted for the largest proportion of the U.S. population, whereas the MHO phenotype accounted for the smallest. In previous studies using the same strict definition of metabolic health, the MUN phenotype varied from 35–45% of the population, and the MHO phenotype ranged from 2.5–5.5% of the population, on average [ 11 , 12 , 23 , 34 ]. In the present study, the proportions of the “intriguing” phenotypes fall within the purviews of prior research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations